MENINGKATKAN KEAKTIVAN DAN HASIL BELAJAR PKn MELALUI PICTURE AND PICTURE UNTUK SISWA KELAS IX SMP - SRI YULIASTINI (LP3M Universitas Muhammadiyah Muara Bungo, 2020)
This research is based on the teaching and learning process of the teacher still using conventional methods and students often play alone in the classroom during learning, take a walk in the classroom, pay less attention to the teacher when explaining the subject matter, leave the classroom without the teacher's permission, lack the courage to ask questions. as well as to fellow friends when the learning process takes place. This study aims to describe the increase in learning outcomes of Civics subjects through the use of the Picture and Picture method in grade IXA students of SMP Negeri 6 Muara Bungo Semester 2 in the 2018/2019 academic year. This type of research is a Classroom Action Research (CAR) with a qualitative descriptive approach carried out in two cycles. The results showed that the use of the Picture and Picture method in Civics learning could increase student activity in the pre-cycle only 32.14%, 42.86% in first cycle, and 85% in second cycle, and the number of students who completed increased in the pre-cycle there were 10 students. , cycle I 19 students, and cycle II 28 students.